Analysis of Nursing Student Ability in English Abstract Translation Research - As'ad, Muhammad (English Education and Literature Journal (E-Jou), 2022)
The translation is an activity that increases students' awareness of the similarities and differences between the grammatical structure of the source language and the target language. Reveals that for a good translation to achieve or meet certain factors such as accuracy, readability, and acceptability. The difference in grammatical structure between the source language and the target language often results in some changes in meaning during the translation process. This research find out the student’s ability in English translation and also the accuracy, readability, and acceptability of the results of abstract translations. Method in this research was descriptive qualitative research with total number of population 80 student’s abstract translations.  The results of research on students' ability to translate from Indonesian into English in terms of accuracy is the total score 16.2, readability total score 17.4, and acceptability is 17.4%. the percentage of the mean score 95.6% with very excellent category. From the analysis of students' abilities in translating from Indonesia to English, the authors found that 80 students who translated abstracts achieved a very good level/excellent. In general, the author concludes that the ability of undergraduate nursing study program students in the 2020/2021 academic year in translating Indonesian into English was very good. Keywords: abstract, nursing student, translation